A low-concentration sodium salt solution, a preparation method and application thereof

CN122907732APending Publication Date: 2026-10-13NANJING UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611382497.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但前者存在黏度大、电导率低、成本高等问题,后者则受限于稀释剂选择少、体系复杂且成本较高

Benefits of technology

[0020]1、本发明提供的低浓度钠盐溶液用于钠离子电池电解液,突破了传统高压钠离子电池电解液依赖高浓度钠盐的技术路径,通过采用0.05~1mol/L的超低浓度钠盐设计,显著降低了电解液的原材料成本,提升了高压下的循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907732A_ABST
    Figure CN122907732A_ABST
Patent Text Reader

Abstract

The application discloses a low-concentration sodium salt solution and a preparation method and application thereof, and belongs to the technical field of sodium ion batteries. The solution comprises sodium salt and a mixed solvent. The concentration of the sodium salt in the solution is 0.05-1 mol / L. The mixed solvent comprises a cyclic carbonate, an aliphatic dinitrile and a fluorinated phosphate. Through the synergistic effect of the low-concentration sodium salt and the specific ternary solvent system, the strong adsorption of the aliphatic dinitrile to the transition metal on the positive electrode side and the strong coordination of sodium ions, the interface double electric layer and the solvation structure are regulated and the oxidation of the cyclic carbonate is reduced, and the fluorinated phosphate is used to promote the construction of the stable interface film, so that the problem of poor high-pressure stability of the low-concentration electrolyte is effectively solved, the cycle life of the battery at high voltage is significantly improved, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery electrolyte technology, specifically relating to a low-concentration sodium salt solution, its preparation method, and its application. Background Technology

[0002] Sodium-ion batteries have attracted widespread attention in the field of large-scale energy storage due to the abundant reserves of sodium, low cost, high safety, and strong wide temperature adaptability. However, the large radius (~0.102 nm) and atomic mass (approximately 23 g / mol) of sodium ions result in low specific capacity and energy density, limiting their practical applications. Layered transition metal oxides (such as O3-type NaNi) 0.33 Fe 0.33 Mn 0.33 O2, P2 type Na 0.67 Ni 0.33 Mn 0.67 O2, etc., are among the most promising cathode materials due to their high specific capacity (typically reaching 100–140 mAh / g). However, to fully utilize the specific capacity of layered cathodes, the charging cutoff voltage needs to be increased to 4.2V or even 4.4V (vs. Na). + The voltage is above 4.0V (~4.0V), which exceeds the electrochemical stability window of traditional carbonate-based electrolytes, leading to serious interfacial side reactions: (1) structural phase transition, oxygen evolution, and transition metal dissolution; (2) transition metal-catalyzed electrolyte decomposition; and (3) CEI / SEI film failure. This will accelerate capacity decay and seriously affect the cycle performance of the battery.

[0003] Currently, in the field of sodium-ion battery technology, to match the high-voltage platform of cathode materials such as layered oxides and suppress electrolyte oxidation and decomposition, existing technologies typically employ strategies such as high-concentration electrolytes, locally high-concentration electrolytes, and functional additives to address the high-voltage challenge. Among these, the high-concentration electrolyte (concentration far exceeding 1 mol / L) and locally high-concentration electrolyte (not less than 1.0 mol / L) strategies improve oxidation stability by reducing the coordination of free solvent molecules and enhancing the coordination of anions. However, the former suffers from high viscosity, low conductivity, and high cost, while the latter is limited by a limited selection of diluents, complex systems, and high costs. Functional additives (such as boron-, sulfur-, and phosphorus-containing additives) can preferentially oxidize to form a protective film on the cathode surface; however, they are consumed rapidly under high voltage, and their long-term cycle stability remains insufficient.

[0004] In summary, existing technologies generally suffer from the following limitations: sodium salt concentrations are too high, and no ultra-low concentration designs below 0.5 mol / L have been explicitly disclosed; solutions to high-voltage issues primarily rely on increasing sodium salt concentrations or adding functional additives, which increases formulation costs and system complexity. Therefore, there is an urgent need for a sodium-ion battery electrolyte system that can maintain excellent high-voltage stability even under low-concentration conditions. Summary of the Invention

[0005] This invention provides a low-concentration sodium salt solution, its preparation method, and its application. The prepared solution is used as an electrolyte in sodium-ion batteries, achieving precise control and interface protection of the positive electrode interface double layer and solvation structure under low sodium salt concentration, thus balancing the low cost and excellent high-voltage cycle performance of sodium-ion batteries.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A low-concentration sodium salt solution includes a sodium salt and a mixed solvent; the concentration of the sodium salt in the solution is 0.05~1 mol / L; the mixed solvent includes cyclic carbonates, aliphatic dinitriles and fluorophosphates.

[0008] The above scheme limits the sodium salt concentration to a low range of 0.05~1 mol / L and uses a specific ternary mixed solvent system composed of cyclic carbonate, aliphatic dionitrile and fluorophosphate. Under low concentration conditions, the strong adsorption of aliphatic dionitrile to the positive electrode transition metal ions and the strong coordination of sodium ions displace cyclic carbonate into the interfacial double layer and solvation shell on the positive electrode side. At the same time, fluorophosphate promotes the preferential film formation of anions at the positive electrode interface, thereby significantly reducing the cost of electrolyte while effectively inhibiting the oxidative decomposition of solvent molecules under high pressure.

[0009] In one embodiment, the concentration of the sodium salt in the solution is 0.1~0.3 mol / L, most preferably 0.2 mol / L.

[0010] In one embodiment, the sodium salt includes at least one of sodium hexafluorophosphate, sodium difluorooxalate borate, sodium difluorosulfonamide, sodium perchlorate, sodium ditrifluoromethanesulfonamide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorooxalate borate, and sodium trifluoroacetate.

[0011] In one implementation, with the total molar amount of the mixed solvent being 100%, the molar percentage of the cyclic carbonate is 30%–65%, the molar percentage of the aliphatic dionitrile is 15%–55%, and the molar percentage of the fluorophosphate is 10%–45%. This range ensures a synergistic effect among the three solvent components: the aliphatic dionitrile preferentially adsorbs onto the transition metal sites on the surface of the cathode material, occupying the interfacial electric double layer, and simultaneously preempts Na coordination in the solvation structure, reducing the entry of cyclic carbonate into the interfacial electric double layer and solvation shell, thus reducing the probability of cyclic carbonate molecules reaching the cathode interface and being oxidized; the fluorophosphate promotes the construction of a barrier by anions at the cathode interface, decomposing the generated NaF-rich inorganic CEI film, effectively blocking subsequent oxidation; the cyclic carbonate exists in the minimum necessary amount to maintain basic ion conductivity and ensure the quality of the anode SEI; the low-concentration design further amplifies the above effects, significantly reducing the total number of solvent molecules reaching the cathode per unit time.

[0012] In one embodiment, the cyclic carbonate includes at least one selected from ethylene carbonate, propylene carbonate, butene carbonate, ethylene ethylene carbonate, and glycerol carbonate; the aliphatic dinitrile includes at least one selected from malononitrile, succinic anionizer, glutaronitrile, adiponitrile, heptacyanide, caprylic anionizer, nonadionitrile, decanonitrile, undecanedionitrile, dodecanedionitrile, tetradecanedionitrile, 2-methylglutaronitrile, and 2-ethylsuccinic anionizer; and the fluorophosphate includes tris(2,2,2-trifluoroethyl) phosphate, diisopropyl fluorophosphate, and bis(2,2, At least one of the following: 2-trifluoroethyl)chlorophosphate, tris(1,1-dihydroheptafluorobutyl)phosphate, tris(m-trifluoromethylphenyl)phosphate, bis(m-trifluoromethylphenyl)(1,1-dihydrotrifluoroethyl)phosphate, 2,2,3,3-tetrafluorotetramethylene-1,4-di(bis-2,2,2-trifluoroethyl)phosphate, bis[2-(perfluorohexyl)ethyl]phosphate, tetramethylfluorourea hexafluorophosphate, dimethyl fluorophosphate, and diethyl (1,1,2,3,3-pentafluoroprop-2-en-1-yl)phosphonate.

[0013] In one embodiment, the cyclic carbonate is ethylene carbonate, the aliphatic dinitrile is adiponitrile, and the fluorophosphate is tris(2,2,2-trifluoroethyl) phosphate; the molar ratio of ethylene carbonate, adiponitrile, and tris(2,2,2-trifluoroethyl) phosphate is (1.5~2.5):(0.5~1.5):(0.5~1.5); preferably, the molar ratio of ethylene carbonate, adiponitrile, and tris(2,2,2-trifluoroethyl) phosphate is 2:1:1.

[0014] The method for preparing the above-mentioned low-concentration sodium salt solution includes the following steps:

[0015] Under an inert atmosphere, all solvents except the cyclic carbonate are dehydrated by soaking in a molecular sieve. The cyclic carbonate is heated to a liquid state, and the mixture is homogeneous to obtain a mixed solvent. The sodium salt is then dissolved in the mixed solvent to obtain the low-concentration sodium salt solution. This method is simple, operates under mild conditions, is suitable for large-scale industrial production, and effectively avoids the influence of moisture and oxygen on the low-concentration electrolyte system.

[0016] In one embodiment, the water and oxygen content of the inert atmosphere are both less than 0.1 ppm; in the dissolution step, the temperature is 25~40℃ and the stirring time is 1~3 hours.

[0017] The aforementioned low-concentration sodium salt solution can be used as an electrolyte in sodium-ion batteries with high-voltage layered oxide cathodes.

[0018] The sodium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte. The electrolyte is a low-concentration sodium salt solution as described above, or prepared using the preparation method described above. Benefiting from the unique design of the aforementioned low-concentration sodium salt solution system, this sodium-ion battery can achieve stable long-cycle operation at high cutoff voltage, while also possessing the advantage of low cost.

[0019] Beneficial effects: This invention provides a low-concentration sodium salt solution, its preparation method, and its application, which have the following advantages compared with the prior art:

[0020] 1. The low-concentration sodium salt solution provided by this invention is used as an electrolyte for sodium-ion batteries, breaking through the traditional technical path of relying on high-concentration sodium salts for high-voltage sodium-ion battery electrolytes. By adopting an ultra-low concentration sodium salt design of 0.05~1mol / L, the raw material cost of the electrolyte is significantly reduced and the cycle performance under high voltage is improved.

[0021] 2. This invention constructs a ternary co-solvent system composed of cyclic carbonates, aliphatic dionitriles, and fluorophosphates. Utilizing the strong adsorption of aliphatic dionitriles to the cathode transition metal under low concentration conditions and the strong coordination competition mechanism of sodium ions, it effectively reduces the probability of easily oxidized cyclic carbonate molecules entering the interfacial electric double layer and the sodium ion solvation shell, thereby reducing the tendency for oxidation and decomposition at the cathode interface from the source. Simultaneously, the fluorophosphates promote the decomposition of anions on the cathode surface to form a dense CEI film rich in inorganic fluorides, further blocking direct contact between the electrolyte and the cathode. This triple synergistic mechanism of "interfacial barrier effect + solvation structure regulation + interfacial film formation" enables the low-concentration electrolyte to maintain excellent electrochemical stability and long cycle life even under a high cutoff voltage of 4.4V, solving the industry problem of poor high-voltage resistance in low-concentration electrolytes. Attached Figure Description

[0022] Figure 1These are linear scanning voltammetric characteristic curves of three electrolytes in embodiments of the present invention;

[0023] Figure 2 This is a comparison chart of the cycling performance of NFM||HC batteries with different electrolytes in the embodiments of the present invention;

[0024] Figure 3 This is a comparison curve of the cycling performance of different electrolyte systems in the embodiments of the present invention. Detailed Implementation

[0025] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments:

[0026] Example 1

[0027] This embodiment provides a low-concentration sodium salt solution, comprising a sodium salt and a mixed solvent; wherein the concentration of the sodium salt in the solution is 0.05~1 mol / L. The mixed solvent comprises cyclic carbonates, aliphatic dinitriles, and fluorophosphates. This embodiment constructs a basic electrolyte system suitable for high-voltage sodium-ion batteries through a specific combination of the above components, aiming to verify the universality and feasibility of this superposition formulation architecture under a wide concentration range and a wide range of solvent ratios.

[0028] This embodiment provides a specific formulation example. Sodium hexafluorophosphate is selected as the sodium salt, ethylene carbonate as the cyclic carbonate, adiponitrile as the aliphatic dinitrile, and tris(2,2,2-trifluoroethyl) phosphate as the fluorophosphate. The three solvents are mixed in a molar ratio of 3:2:1, and then sodium hexafluorophosphate is added and stirred until completely dissolved, resulting in a final electrolyte concentration of 0.4 mol / L for sodium hexafluorophosphate. It should be understood that this formulation is only an illustrative example and not a limiting provision. As long as the sodium salt concentration falls within the range of 0.05~1 mol / L, and the mixed solvent consists of cyclic carbonate, aliphatic dinitrile, and fluorophosphate, it falls within the scope of protection of this invention. For example, the sodium salt can also be other soluble sodium salts such as sodium difluorooxalate borate or sodium difluorosulfonamide; the cyclic carbonate can also be propylene carbonate; the aliphatic dinitrile can also be succinic anionyl or glutaronitrile; and the fluorophosphate can also be other fluorinated alkyl phosphate derivatives.

[0029] Unlike conventional high-concentration (1–2 mol / L) electrolytes, ultra-low concentration sodium salts are one of the key features of this invention. Under low concentration conditions, each Na + The number of available solvent molecules for coordination increases relatively, but because ADN has two strong coordination ends (-C≡N), it has a strong affinity for the adsorption of transition metal ions on the positive electrode surface, thus competing for the transition metal ions on the positive electrode surface and Na+ in the electrolyte. +Coordination sites reduce the entry of ECs into the interfacial electric double layer and solvation shell, thus decreasing the probability of EC molecules reaching the positive electrode interface. The NaF-rich inorganic CEI film generated by TFP-promoted anion decomposition also effectively blocks subsequent oxidation. ECs exist in the minimum necessary amount to maintain basic ion conductivity and ensure the quality of the negative electrode SEI. The low-concentration design further amplifies these effects, significantly reducing the total number of solvent molecules reaching the positive electrode per unit time. Existing technologies typically reduce the number of free solvent molecules by increasing the concentration, but this invention takes the opposite approach, utilizing a triple synergistic mechanism of "interfacial blocking effect + solvation structure regulation + interfacial film formation" to achieve a similar solvation structure regulation effect, achieving high-pressure stability while reducing raw material costs.

[0030] Example 2

[0031] This embodiment, based on Example 1, further specifies the specific types of sodium salts, the specific chemical substances of each component in the mixed solvent, and the optimal molar ratio among the three. Specifically, the sodium salt includes at least one of sodium hexafluorophosphate, sodium difluorooxalate borate, sodium bis(fluorosulfonyl)imide, sodium perchlorate, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium bis(oxalate borate), and sodium trifluoroacetate. These sodium salts exhibit excellent electrochemical stability and solubility in the low-concentration ternary solvent system of this invention. Among them, sodium hexafluorophosphate is the preferred choice for industrial applications due to its balanced overall performance and relatively low cost; sodium difluorooxalate borate and sodium bis(fluorosulfonyl)imide can be used as high-performance alternatives to meet different battery design requirements. Meanwhile, the cyclic carbonates include at least one of ethylene carbonate, propylene carbonate, butene carbonate, ethylene ethylene carbonate, and glycerol carbonate, preferably ethylene carbonate; the aliphatic dinitrile includes at least one of malononitrile, succinic anionitrile, glutaronitrile, adiponitrile, heptacyanide, caprylic anionitrile, nonadionitrile, decanonitrile, undecanedionitrile, dodecanedionitrile, tetradecanedionitrile, 2-methylglutaronitrile, and 2-ethylsuccinic anionitrile, preferably adiponitrile; and the fluorophosphates include tris(2,2,2-trifluoroethyl) phosphate, diisopropyl fluorophosphate, and bis(2,2,2-trifluoroethyl) chlorophosphate. At least one of the following: phosphate ester, tris(1,1-dihydroheptafluorobutyl) phosphate, tris(m-trifluoromethylphenyl) phosphate, bis(m-trifluoromethylphenyl)(1,1-dihydrotrifluoroethyl) phosphate, 2,2,3,3-tetrafluorotetramethylene-1,4-bis(bis-2,2,2-trifluoroethyl) phosphate, bis[2-(perfluorohexyl)ethyl] phosphate, tetramethylfluorourea hexafluorophosphate, dimethyl fluorophosphate, and diethyl (1,1,2,3,3-pentafluoroprop-2-en-1-yl)phosphonate, preferably tris(2,2,2-trifluoroethyl) phosphate. Ethylene carbonate, as a high dielectric constant solvent, not only ensures the effective dissociation of sodium salt but is also a key component in constructing a stable negative electrode solid electrolyte interfacial film. Adiponitrile, with its strong coordination ability and wide electrochemical window due to its double-terminated cyano groups, becomes the core component for regulating the interfacial electric double layer and solvation structure. Tris(2,2,2-trifluoroethyl) phosphate possesses multiple functions, including a wide electrochemical window and promoting anionic CEI film formation. Based on this, the molar ratio of ethylene carbonate, adiponitrile, and tris(2,2,2-trifluoroethyl) phosphate is (1.5~2.5):(0.5~1.5):(0.5~1.5); preferably, the molar ratio of ethylene carbonate, adiponitrile, and tris(2,2,2-trifluoroethyl) phosphate is 2:1:1. This specific ratio represents the optimal balance point for achieving the ternary synergistic effect, maximizing the efficiency of interfacial protection, solvation, and regulation of the interfacial electric double layer.

[0032] To fully verify the technical effectiveness of the optimal combination described above, this embodiment prepared the electrolyte and conducted tests according to the following specific steps. First, in an argon glove box with water and oxygen content both less than 0.1 ppm, all solvents except EC were dehydrated by soaking in molecular sieves. The EC solid was heated to liquid state on a stirring table at 60°C. Each component was accurately weighed according to the molar ratio NaPF6:EC:ADN:TFP = 0.5:2:1:1 and placed in a dry container. Subsequently, the electrolyte was magnetically stirred at 30°C for 2 hours until completely dissolved, yielding the electrolyte. The concentration of sodium hexafluorophosphate was determined to be approximately 0.2 mol / L. This preparation process strictly adhered to the requirements of an inert atmosphere and thorough stirring, ensuring the uniformity and stability of the components in the low-concentration system.

[0033] The electrolyte provided in this embodiment achieves excellent high-voltage performance at low concentrations due to the underlying microscopic mechanism of precise synergy between the ternary components and the amplification effect of the low-concentration environment. At a low concentration of 0.2 mol / L, each sodium ion has relatively ample coordination space for solvent molecules. At this point, the cyano groups at both ends of the adiponitrile molecule, with their strong affinity for transition metal ions and sodium ions, preferentially occupy key sites in the interfacial electric double layer and the sodium ion solvation shell, effectively displacing ethylene carbonate molecules from these layers. This effect reduces the probability of easily oxidized ethylene carbonate molecules migrating to the cathode surface with sodium ions, significantly lowering the tendency for oxidative decomposition under high pressure. Simultaneously, although tris(2,2,2-trifluoroethyl) phosphate participates in solvation to a lower degree, its electrochemical window is stable and it promotes the decomposition of anions at the cathode interface, forming a dense CEI film rich in inorganic components such as sodium fluoride. This CEI barrier effectively prevents direct contact between the electrolyte and the cathode material, suppressing continuous side reactions. The low-concentration design further amplifies the effects of the three mechanisms mentioned above: due to the reduction in the total number of solvent molecules per unit volume, the flux of active solvent reaching the cathode interface decreases significantly, making the coordination competition advantage of adiponitrile and the high-voltage stability advantage of tris(2,2,2-trifluoroethyl) phosphate more prominent, thus achieving a synergistic effect of "1+1+1>3".

[0034] Electrochemical test results strongly confirm the validity of the above mechanism. For example... Figure 1 The linear sweep voltammetric curves shown indicate that the oxidative decomposition initiation potential of the electrolyte provided in this embodiment on the aluminum foil working electrode exceeds 5 V (vs. Na). +The sodium hexafluorophosphate (Na) electrolyte exhibits extremely low current response and no significant oxidation peak across the entire test voltage range, demonstrating an extremely wide electrochemical stability window. In contrast, under the same battery assembly and testing conditions (test conditions: aluminum foil as the working electrode, metallic sodium as the counter and reference electrode, scan rate 1 mV / s), conventional 1 mol / L sodium hexafluorophosphate / propylene carbonate electrolyte and 1 mol / L sodium hexafluorophosphate / ethylene carbonate electrolyte show significant oxidation current peaks at approximately 4.0 V and 4.3 V, respectively, indicating that they inevitably undergo severe decomposition at a high voltage of 4.4 V.

[0035] Example 3

[0036] This embodiment provides a sodium-ion battery, including a positive electrode, a negative electrode, a separator, and an electrolyte. The electrolyte is a low-concentration sodium salt solution as provided in the previous embodiments. This embodiment aims to verify the aforementioned low-concentration ternary solvent sodium salt solution system in a real battery device environment to demonstrate the effectiveness of this technical solution in solving the high-voltage, long-cycle technical problem in practical applications. It should be understood that although this embodiment uses specific electrode materials and battery structures as examples, this is merely an exemplary choice for verifying the technical effect and is not a limitation on the scope of protection of this invention. As long as the sodium-ion battery uses the electrolyte system or preparation method defined in this invention, regardless of any changes in its specific positive and negative electrode material system or packaging form, it falls within the protection scope of this invention.

[0037] Specifically, the battery assembly in this embodiment is as follows: the positive electrode active material is selected from O3-type layered transition metal oxide NaNi. 0.33 Fe 0.33 Mn 0.33 O2 (NFM) is a material characterized by high specific capacity but poor high-voltage stability. Hard carbon is selected as the negative electrode active material, as it has a low sodium storage potential and is widely available, making it a mainstream negative electrode material for sodium-ion batteries. A glass fiber separator is used to ensure good wettability and ion permeability in low-concentration electrolyte systems. The battery is packaged as a CR2032 coin cell, with the electrolyte volume controlled within an appropriate range to ensure sufficient wetting. It should be emphasized that the above-mentioned positive electrode material is only an example; the electrolyte of this invention is also applicable to other sodium-ion battery positive electrode materials such as P2-type layered oxides, polyanionic compounds, or Prussian blue-based materials. The negative electrode is not limited to hard carbon and can be extended to soft carbon, alloys, or conversion-type negative electrode materials. The battery form can also be cylindrical, square aluminum-cased, or pouch cells, etc., for industrial mass production.

[0038] The electrochemical performance testing was conducted under stringent high-voltage conditions. The test conditions were: charge / discharge voltage window 1.5–4.4 V (vs. Na). +After activation at charge / discharge rates of 0.1C and 0.33C for several cycles, the charge / discharge rate was maintained at 1C during subsequent cycles at a test temperature of 25°C. This high cutoff voltage of 4.4 V significantly exceeds the electrochemical stability window of traditional carbonate-based electrolytes. Under these conditions, the NFM||HC full cell assembled using the optimal electrolyte (NaPF6 concentration approximately 0.2 mol / L, EC:ADN:TFP molar ratio 2:1:1) exhibits excellent high-voltage, long-cycle stability. Figure 2 As shown, after 200 cycles at a high voltage of 4.4 V, the battery still maintains a discharge specific capacity of over 80 mAh / g, a capacity retention rate of 83%, and a coulombic efficiency of over 99.9%. This data indicates that the low-concentration ternary solvent system of this invention successfully constructs a stable positive electrode electrolyte interface film and a negative electrode solid electrolyte interface film, effectively suppressing continuous side reactions under high voltage and achieving reversible sodium ion insertion and extraction.

[0039] In contrast. Figure 2 The paper also demonstrates the degradation curves of batteries assembled using conventional electrolytes under the same high-voltage conditions. Comparative Example 1, using a 1 mol / L NaPF6 / PC electrolyte, experienced rapid degradation in the early stages of cycling, with a capacity of only about 10 mAh / g remaining after 200 cycles, a retention rate as low as 7%. This was attributed to the severe oxidative decomposition of the PC solvent and its erosion of the cathode material under 4.4 V high voltage. Comparative Example 2, using a 1 mol / L NaPF6 / EC electrolyte, showed slightly better initial performance, but its capacity also decreased to the 40-50 mAh / g range after 200 cycles, with a retention rate of 51%. This indicates that even though EC has good film-forming properties, it cannot withstand the long-term impact of 4.4 V high voltage in the presence of high-concentration free solvent molecules. This demonstrates that in real-world battery applications, simply increasing the sodium salt concentration or using a single carbonate solvent is insufficient to meet the requirements of long-term cycling at 4.4 V high voltage. The present invention, through its "low concentration + ternary solvent synergy" design, exhibits irreplaceable technical advantages in practical battery applications.

[0040] also, Figure 3This further verifies the compatibility of the electrolyte system of this invention with different sodium salt types and its universality in practical batteries. When sodium difluorooxalate borate (NaDFOB) is used instead of sodium hexafluorophosphate while keeping other components unchanged, the resulting battery retains approximately 80% of its capacity after 200 cycles under the same 4.4 V high-voltage test conditions, and even shows a slightly better specific capacity than the NaPF6 system throughout the entire cycle. This indicates that the core technical concept of this invention lies in the synergistic mechanism of interfacial double layer, solvation regulation, and interfacial film formation among cyclic carbonates, aliphatic dinitrile, and fluorophosphates under low-concentration conditions, rather than relying on a specific conductive salt. This broad adaptability to different sodium salt types provides ample room for flexible adjustment of the formulation according to cost and specific performance requirements in actual production.

[0041] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art, within the technical scope disclosed in this invention, can easily conceive of variations or substitutions such as equivalent substitution of sodium salt types, adjustment of the proportion of mixed solvent components, addition or subtraction of functional additives, or changes in battery packaging methods, based on the aforementioned synergistic mechanism and solvation structure control strategy of the low-concentration ternary solvent system. All such variations or substitutions should be covered within the scope of protection of this invention. Therefore, the scope of protection of this invention should be determined by the scope of the claims.

Claims

1. A low-concentration sodium salt solution, characterized in that, It includes a sodium salt and a mixed solvent; the concentration of the sodium salt in the solution is 0.05~1 mol / L; the mixed solvent includes cyclic carbonates, aliphatic dinitriles and fluorophosphates.

2. The low-concentration sodium salt solution according to claim 1, characterized in that, The concentration of the sodium salt in the solution is 0.1~0.3 mol / L.

3. The low-concentration sodium salt solution according to claim 1 or 2, characterized in that, The sodium salt includes at least one of sodium hexafluorophosphate, sodium difluorooxalate borate, sodium difluorosulfonamide, sodium perchlorate, sodium ditrifluoromethanesulfonamide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorooxalate borate, and sodium trifluoroacetate.

4. The low-concentration sodium salt solution according to claim 1, characterized in that, Based on the total molar percentage of the mixed solvent being 100%, the molar percentage of the cyclic carbonate is 30% to 65%, the molar percentage of the aliphatic dionitrile is 15% to 55%, and the molar percentage of the fluorophosphate is 10% to 45%.

5. The low-concentration sodium salt solution according to claim 1 or 4, characterized in that, The cyclic carbonate includes at least one selected from ethylene carbonate, propylene carbonate, butene carbonate, ethylene ethylene carbonate, and glycerol carbonate; the aliphatic dinitrile includes at least one selected from malononitrile, succinic anionitrile, glutaronitrile, adiponitrile, heptacyanide, caprylic anionitrile, nonadionitrile, decanonitrile, undecanedionitrile, dodecanedionitrile, tetradecanedionitrile, 2-methylglutaronitrile, and 2-ethylsuccinic anionitrile; the fluorophosphate includes tris(2,2,2-trifluoroethyl) phosphate, diisopropyl fluorophosphate, and bis(2,2,2-trifluoroethyl) phosphate. At least one of the following: ethyl chlorophosphate, tris(1,1-dihydroheptafluorobutyl) phosphate, tris(m-trifluoromethylphenyl) phosphate, bis(m-trifluoromethylphenyl)(1,1-dihydrotrifluoroethyl) phosphate, 2,2,3,3-tetrafluorotetramethylene-1,4-di(bis-2,2,2-trifluoroethyl) phosphate, bis[2-(perfluorohexyl)ethyl] phosphate, tetramethylfluorourea hexafluorophosphate, dimethyl fluorophosphate, and diethyl (1,1,2,3,3-pentafluoroprop-2-en-1-yl)phosphonate.

6. The low-concentration sodium salt solution according to claim 5, characterized in that, The cyclic carbonate is ethylene carbonate; the aliphatic dinitrile is adiponitrile; and the fluorophosphate is tris(2,2,2-trifluoroethyl) phosphate.

7. The method for preparing the low-concentration sodium salt solution according to any one of claims 1-6, characterized in that, Includes the following steps: Under an inert atmosphere, solvents other than cyclic carbonates are soaked in molecular sieves to remove water, the cyclic carbonates are heated to liquid, and after being mixed evenly, a mixed solvent is obtained. The sodium salt is then dissolved in the mixed solvent to obtain the low-concentration sodium salt solution.

8. The method for preparing a low-concentration sodium salt solution according to claim 7, characterized in that, The water and oxygen content of the inert atmosphere are both less than 0.1 ppm.

9. The method for preparing a low-concentration sodium salt solution according to claim 7, characterized in that, Before preparation, all solvents must be soaked in a molecular sieve to remove water. The temperature during the dissolution step is 25~40℃, and the stirring time is 1~3 hours.

10. The application of the low-concentration sodium salt solution according to any one of claims 1-6, characterized in that, The low-concentration sodium salt solution is used as the electrolyte in sodium-ion batteries with high-voltage layered oxide cathodes.